(untitled) - Calano, James (Hoboken, N.J., 2005)
In Make Your Move, expert Jimmy Calano draws on his vast experience in the self-development field and distills the essence of his thoughts on how to purposefully and enthusiastically achieve a fuller life. Readers will quickly discover ways to move forward with compelling chapters about triumphing over procrastination, making things happen, dusting off dreams, nourishing their minds, dealing with disappointment, and more. Each chapter is divided into attention-grabbing stories and anecdotes, rewards for adopting the advocated behaviors, and how-tos for implementing the recommendations. With its inviting style and easy-to-assimilate wisdom, Make Your Move gives readers the skills—and the inspiration—to do more with their lives.
Keywords: Success,Self-actualization (Psychology),Sự thành công,Sự tự khẳng định mình (Tâm lý học); Psychological aspects,Khía cạnh tâm lý